Mobility and Development, Spring 2022 : Innovations, Policies and Practices - World Bank (Washington, DC: World Bank, 2022)
The traditional approach to valuing the benefits of transport investments overlooks their wider economic impacts. Traditional cost-benefit analysis of road projects focuses on estimating the value of time savings that result from upgrading infrastructure to improve the volume and speed of transit. While these benefits are important and have often been enough in and of themselves to justify significant road investments, they overlook the fundamental ways in which transport improvements reshape patterns of economic activity, or in a sense the value of what is moving along any road corridor. In that sense, the traditional approach underestimates the true economic impact of roads. New spatial data can bring new light on the welfare gains of transport investments for households and firms. The increasing availability of spatial data for infrastructure networks, and household and firm surveys has greatly improved the way we investigate whether infrastructure investments have an impact on prices, jobs, consumption, or productivity. A new body of emerging research applies these novel techniques to examine the links between roads, complementary infrastructures, and development extensively across many African countries. This article will review the main findings of this new research in a nontechnical format accessible to practitioners, making the emerging evidence readily available to a wider audience. The research has been sponsored by the Chief Economist’s Office of the Infrastructure Vice Presidency of the World Bank, in partnership with the Transport Global Practice as well as Infrastructure (INF) and Equitable Growth, Finance and Institutions (EFI) teams in the Africa East and West Regions and the Office of the Director for Regional Integration in Africa.